Konsep Pembaruan Nous Berdasarkan Surat Roma 12:1-2 - Hendi Hendi; Eka Nur Cahyani (Jurnal Teologi Gracia Deo, 2021)
The Concept of Renewal Nous in Christ Based on Romans 12: 1-2. This article discussing the renewal of nous in Christ through a syntactic and semantic approach to text analysis, namely the focus on the text itself, interactions with other texts and the writings of the Church Fathers. The renewal of nous is the starting point of the consequences of the journey of the believer after being baptized and becoming a Christian is to perfect the image of God in him which continues to be perfected until he becomes like Christ. There are two main points of discussion, namely the process of renewing Nous and the results of renewing Nous. The process of renewing nous is kenosis by offering the body and not becoming conformed to the world as a form of turning off the desires of the flesh so that it is no longer sold in sin. The result of renewal is having a front (the mind of Christ). Only Christians who renew their nous have the mind of Christ, guarding their souls with all vigilance to the likeness of His image. Abstrak Konsep Pembaruan Nous Di dalam Kristus Berdasarkan Surat Roma 12:1-2. Artikel ini membahas tentang pembaruan nous di dalam Kristus melalui pendekatan analisis teks secara sintaksis dan semantis yaitu fokus pada teks itu sendiri, interaksi dengan teks-teks lain dan tulisan para Bapa Gereja. Pembaruan nous adalah titik awal konsekuensi dari perjalanan orang percaya setelah dibaptis dan menjadi orang Kristen adalah menyempurnakan gambar Allah di dalam dirinya yang terus disempurnakan sampai menjadi serupa dengan Kristus. Ada 2 pokok pembahasan yaitu proses pembaruan nous dan hasil dari pembaruan nous. Proses pembaruan nous adalah kenosis dengan mempersembahkan tubuh dan tidak menjadi serupa dengan dunia sebagai wujud dari mematikan keinginan daging sehingga tidak lagi terjual di dalam dosa. Hasil dari pembaruan nous adalah memiliki fronew (pikiran Kristus). Hanya orang Kristen yang memperbarui nousnya yang memiliki pikiran Kristus, menjaga jiwanya dengan segala kewaspadaan hingga serupa gambar dan rupaNya.